Thrombin generation test in children and adolescents with chronic liver disease. Issue 2 (February 2015) - Magnusson, Maria; Berndtsson, Maria; Fischler, Björn; Petrini, Pia; Schulman, Sam; Renne, Thomas; Granath, Anna; Sten-Linder, Margareta; Németh, Antal
Abstract: Introduction: The aim of this study was to evaluate if real-time thrombin generation assay provides additional information to assess the hemostatic balance in children with liver disease as compared to routine coagulation tests. Patients and Methods: Sixty-three children with chronic liver disease were enrolled at our tertiary referral center for pediatric hepatology, eight whose routine coagulation tests gave abnormal results (Group A) and 55 whose test results were normal (Group B). Abnormal routine coagulation test was defined as at least one of the following: international normalized ratio≥ 1.4, activated partial thromboplastin time > 44 sec., fibrinogen < 1.5 g/L. Platelet-poor plasma was analyzed with the fluorogenic Calibrated Automated Thrombogram to test for thrombin generation, including endogenous thrombin potential. Further, routine coagulation tests and plasma levels of pro- and anticoagulant factors were measured. Twenty age-matched children without liver disease served as controls. Results: The endogenous thrombin potential in the 55 patients with normal routine coagulation tests was not significantly different from that in controls. Group A had significantly lower levels not only of procoagulant factors (II, V, VII, X) but simultaneously also of the anticoagulant factors antithrombin, protein S free, and protein C. These patients had a reduced endogenous thrombin potential compared to Group B, in agreement with their routine coagulation test results. Conclusion: Thrombin generation analysis seems to give information on the hemostatic balance consistent with routine coagulation test results in children with liver disease. Further development and clinical evaluation of the method are warranted. Highlights: Thrombin generation was studied in pediatric patients with chronic liver disease. Patients with normal routine coagulation tests had ETP results similar to those of healthy controls. Patients with abnormal routine coagulation tests had significantly lower ETP. Patients with abnormal routine coagulation tests had lower levels of both pro- and anticoagulant proteins. Further development and clinical evaluation of the thrombin generation assay are requested.